ANALYSIS AND ASSESSMENT OF THE QUALITY OF NUTRITION OF CHILDREN IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Akhmadkhodzhaeva М.М; Toshmatova G.A.; Mirmukhamedov B.B. (American Journals, 2023)
An analysis of the actual nutrition of preschoolers shows that the diet does not meet the physiological norm, and in the daily diet the amount of meat and meat, milk and dairy products is below the norm. It should be noted that fish and fish products are absent in the diet of children. Analysis of the nutritional value of the diet shows that children receive proteins, fats, vitamin A, calcium, phosphorus, iron and iodine below the recommended norms.
Keywords: preschoolers, nutrition, nutrients, daily ration, proteins, fats and carbohydrates.